Terra-i+ web tools enable non-specialists to calculate climate and environmental metrics on their own data, in confidence - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The current suite of web tools is full functional and dynamic and has been shared with select early test users. In 2022 further refinement will be made based on user feedback and access will be provided on a subscription basis.